Health Care Workers not in the frontline are more frequently carriers of Coronavirus Disease 2019: The Experience of a Tertiary Portuguese Hospital - Eduardo J.F. Santos; Ricardo J.O. Ferreira; Ricardo Batista; Vítor Pinheiro; Andréa A. Marques; Isabel Antunes; António Marques (Elsevier, 2020)
Summary: Background: Health care workers (HCWs) have a high risk of infection with coronavirus disease 2019 (COVID-19), especially those treating patients with confirmed or suspected diagnosis (front-line). Aim: To evaluate the incidence and prevalence of the COVID-19 infection among HCWs and to analyse the risk factors and the clinical characteristics among infected ones. Methods: Observational, retrospective, single-center study (Centro Hospitalar e Universitário de Coimbra, Portugal). Data were collected from March 1 to June 30, 2020. Findings: Overall, 211 (2.63%) out of 8037 HCWs were diagnosed with COVID-19. Most of the infections occurred during the early stage of disease outbreak. Among the infected HCWs, only 20.9% (n=44) were from the front-line. Both front-line and non-front-line HCWs were exposed primarily to patients (48.6% in both groups), but the non-front-line were (presumably) more infected by colleagues (10.8% vs 24.8%, P=0.04). Front-line HCWs performed more family isolation than non-front-line (88.9% vs 82.5%, P>0.05) and presumably less family members were infected in the former group (19.4% vs 26.3%, P>0.05). The proportion of HCWs with asymptomatic infection was statistically significantly lower in the front-line group (2.4% vs 19.9%, P=0.05). Conclusion: The prevention and control actions implemented were effective in mitigating the COVID-19 outbreak; HCW infections occurred mainly in the early stages. Non-front -line HCWs were at a higher risk, warranting specific attention and interventions targeting this group.